1999
DOI: 10.1029/1999ja900336
|View full text |Cite
|
Sign up to set email alerts
|

Form of the anomalous cosmic ray spectrum at the solar wind termination shock

Abstract: Abstract. New insights regarding the form of the accelerated anomalous cosmic ray spectrum at the solar wind termination shock, obtained from solutions of the cosmic ray transport equation, are presented. A simple analytical expression for the spectrum on the shock is derived, and its dependence on the acceleration parameters is shown. Particular attention is paid to the high-energy cutoff of this spectrum. This expression and its parameterization should be applicable for the acceleration of charged particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 19 publications
4
29
0
Order By: Relevance
“…More realistic parameters would yield results that are quantitatively different, but still qualitatively similar. This paper is an extension of the work published in [17,20].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…More realistic parameters would yield results that are quantitatively different, but still qualitatively similar. This paper is an extension of the work published in [17,20].…”
Section: Introductionmentioning
confidence: 82%
“…It was found that for a wide range of parameters [17,20] that the cutoff in the shock spectrum occurs where (6) …”
Section: Transport and Acceleration Of Cosmic Raysmentioning
confidence: 99%
See 1 more Smart Citation
“…Near the equatorial plane, θ > 60 • , this power law persists up to ∼10 MeV nuc −1 in the equatorial plane, where the ACR rollover is observed. This almost exponential decay in intensity is believed to occur predominantly due to the curvature of the TS (Steenberg & Moraal 1999) leading to ineffective Fermi I acceleration above these energies. Near the polar regions however, the spectra exhibit a highly modulated form for E > 0.1 MeV nuc −1 .…”
Section: Latitude Dependent S(θ) and I(θ)mentioning
confidence: 99%
“…With increasing energy, intensities eventually start to fall away almost exponentially. The energy at which this deviation in the power law spectrum occurs is referred to as the cut-off or roll-over energy determined by, amongst others, the curvature of the shock front (Steenberg & Moraal 1999;Langner & Potgieter 2007). The spectra at Earth illustrate the corresponding modulated roll-over intensities; below ∼10 MeV nuc −1 these spectra are dominated by adiabatic cooling giving rise to the well-known j ∝ E spectral shapes.…”
Section: Modelling Results and Discussionmentioning
confidence: 99%